2014
DOI: 10.1371/journal.pone.0111838
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Hypoxia to Treat Anemia: HIF-Stabilizer BAY 85-3934 (Molidustat) Stimulates Erythropoietin Production without Hypertensive Effects

Abstract: Oxygen sensing by hypoxia-inducible factor prolyl hydroxylases (HIF-PHs) is the dominant regulatory mechanism of erythropoietin (EPO) expression. In chronic kidney disease (CKD), impaired EPO expression causes anemia, which can be treated by supplementation with recombinant human EPO (rhEPO). However, treatment can result in rhEPO levels greatly exceeding the normal physiological range for endogenous EPO, and there is evidence that this contributes to hypertension in patients with CKD. Mimicking hypoxia by inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(197 citation statements)
references
References 69 publications
8
185
1
3
Order By: Relevance
“…Similar small preclinical and clinical studies have demonstrated some pleiotropic effects of this class of drug (molidustat corrected anaemia in rat studies and also helped normalise blood pressure; daprodustat was shown to improve cholesterol levels) (82,83). Advantages of this new class of drug include oral administration, low immunogenicity, product stability and possibly lower costs as well as potential cardiovascular benefits (84).…”
Section: Hif-ph Inhibitorsmentioning
confidence: 80%
“…Similar small preclinical and clinical studies have demonstrated some pleiotropic effects of this class of drug (molidustat corrected anaemia in rat studies and also helped normalise blood pressure; daprodustat was shown to improve cholesterol levels) (82,83). Advantages of this new class of drug include oral administration, low immunogenicity, product stability and possibly lower costs as well as potential cardiovascular benefits (84).…”
Section: Hif-ph Inhibitorsmentioning
confidence: 80%
“…However, emerging evidence supports a blood pressure-lowering effect of PHD inhibitors (noted with 3 separate agents) equivalent to that achieved by enalapril [73,74,75]. …”
Section: Hif-phis In the Treatment Of Anemia In Patients With Ckdmentioning
confidence: 99%
“…The most promising are the PHD inhibitors (Table 1) with several compounds already under evaluation in clinical trials. Some of these compounds showed to be well tolerated, corrected anemia in non-dialysis CKD and incident dialysis patients without increasing blood pressure, and also reduced serum hepcidin levels [70][71][72][73]. However, regarding their effects in reducing cardiovascular events and slowing the progression of the renal disease, no data are still available from human studies.…”
Section: Erythropoiesis-stimulating Agents In Ckd-anemiamentioning
confidence: 99%